Beamforcing for Efficient Spectrum Sensing Based TRMS - Vaishnavi, S; Pavithra, A (International Journal of Computer Sciences and Engineering, 2025)
This manuscript shows a novel routing protocol for Active-Inactive networks (AINs) called Signal-to-Interference-plus-Noise-Ratio (SINR). SINR sagaciously coordinates the sending and buffer administration arrangements into a versatile protocol that incorporates a neighborhood organize parameters estimation instrument. It powerfully changes the delivery likelihood for messages as indicated by another metric. In the interim, SINR organizes the sending arrangement and the dropping need in light of their doled out weight. The weight is controlled by the Replication Density (RD), the Message Length (ML), and Message Excess Life Time (MELT). A broad recreation of SINR was done and its execution was contrasted with surely understood AIN routing protocols: PRoPHET, and Epidemic Routing protocols. Reenactment comes about demonstrate that the proposed routing protocol beats them as far as bundle delivery proportion, delivery deferral and message overhead.